Emotions, Empathy, and Engagement with God in Revelation 6: 9-11 - Seal, David (The expository times, 2017)
Very few studies have explored the connection between prayer and religious experience, which are recounted in biblical and extra biblical literature. Religious experience is usually investigated within the categories of visions, auditions or dreams. Often prayer is only considered a ritual for the incubation of a religious or divine experience. This study will explore prayer as a divine experience in the petition by the martyrs in Revelation 6:9-11. We will proceed with this investigation by first, defining empathy and demonstrating its role in allowing a person to connect with another person's experience. Second, because of its importance in empathy, we will define emotions, and then define fear or reverence, lament, hope, and confidence, which are the specific emotions that are communicated in Revelation 6:9-11. Third, we will describe the textual evidence supporting a divine experience for the martyrs. Finally, we will explore how the emotions of lament, reverence, hope, and confidence are invoked in Revelation 6:9-11. These feelings potentially could cause listeners or readers to undergo a similar divine experience as the martyrs.